Biosynthesis of Silver Nanoparticles by Marine Invertebrate (Polychaete) and Assessment of Its Efficacy against Human Pathogens. (20th August 2014) - Singh, Reena; Sahu, Sunil Kumar; Thangaraj, Muthusamy
Abstract : Synthesis of metallic nanoparticles by chemical and physical method makes the process often cumbersome due the usage of toxic and expensive chemicals. The present study reports the biosynthesis of silver nanoparticles using marine invertebrate (polychaete) extract at room temperature. The ultraviolet-visible (UV-Vis) spectroscopy revealed the formation of silver nanoparticles (AgNPs) by exhibiting the typical surface plasmon absorption maximum at 418–420 nm. Structure and composition of AgNPs were analyzed by atomic force microscopy (AFM). Average particle size of AgNPs ranged from 40 to 90 nm, confirmed by scanning electron microscopy (SEM) analysis. The energy-dispersive X-ray spectroscopy (EDX) of the nanoparticles dispersion confirmed the presence of elemental silver signal, whereas X-ray diffraction (XRD) substantiated the crystalline nature of synthesized nanoparticle. Fourier transform infrared spectroscopy (FTIR) spectral analysis showed the presence of amides phenols, ethers, and fatty acids as major biomolecules responsible for the reduction of silver ions. The possible mechanism responsible for the synthesis of AgNPs by these biomolecules was also illustrated by chemical reactions. The synthesized AgNPs showed comparatively good antibacterial activity against the tested human pathogens. This study advocates that not only plants and microbes but also marine invertebrates do have potential for synthesizing nanoparticles by a cost-effective and eco-friendly approach.